2023
DOI: 10.1111/jocn.16810
|View full text |Cite
|
Sign up to set email alerts
|

Vital sign assessment and nursing interventions in medical and surgical patients with rapid response system triggers

Abstract: Aim(s)To explore vital sign assessment (both complete and incomplete sets of vital signs), and escalation of care per policy and nursing interventions in response to clinical deterioration.DesignThis cohort study is a secondary analysis of data from the Prioritising Responses of Nurses To deteriorating patient Observations cluster randomised controlled trial of a facilitation intervention on nurses' vital sign measurement and escalation of care for deteriorating patients.MethodsThe study was conducted in 36 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Results of a contemporary study show a practice change with temperature (Bleyer et al, 2011;Considine, Hutchinson, et al, 2023) and conscious state (Considine, Hutchinson, et al, 2023) now being the most frequently reported missing vital signs.…”
Section: Where and On Whom Will The Research Have An Impact?mentioning
confidence: 98%
See 4 more Smart Citations
“…Results of a contemporary study show a practice change with temperature (Bleyer et al, 2011;Considine, Hutchinson, et al, 2023) and conscious state (Considine, Hutchinson, et al, 2023) now being the most frequently reported missing vital signs.…”
Section: Where and On Whom Will The Research Have An Impact?mentioning
confidence: 98%
“…In hospitals, vital signs are the most commonly collected patient data and are essential in recognising clinical deterioration; however, there is evidence that vital signs are not documented regularly or accurately (Kellett & Sebat, 2017). Studies of vital sign documentation have typically classified documentation as complete or incomplete (Bleyer et al, 2011;Considine, Hutchinson, et al, 2023) and show variability in the frequency with which specific vital signs are documented. The proportion of assessments of 'sets of vital signs' with one or more missing vital sign are reported to range from zero to 41% (Bleyer et al, 2011;Cahill et al, 2011;Chen et al, 2009;Van Leuvan & Mitchell, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations